7 - Wars as Postcolonial African Illness in Uzodinma Iweala’s Beasts of No Nation - Osiki, Omon; Owonibi, Sola; Ojedokun, Oluyinka (Africa Development, 2021)
There has always been a war somewhere in the world among Homo sapiens, allegedly the most advanced species in the universe. In Africa, right on the heels of colonialism and the celebration of independence loom the devastation and desolation of war. It is not a sweeping statement to conclude that everywhere colonialism has touched in Africa and let go, ruthless tribal wars have followed suit. The thematic preoccupation of the post-war literature is the training of children, mostly boys, to kill, in the form of the phenomenon of the ‘child soldier’. This article argues that one of the extreme cases of geopolitical illness that Africa suffers is the prominence of war in the turbulent journeys of her nation-states to nationhood. The article also examines the psychological implications of wars and bloodshed on the lives of children, who ought to be protected, which results in illness behaviours. We explore these themes with close reference to Uzodinma Iweala’s Beasts of No Nation.